School-based training program on classroom management for beginning science teachers - Urbiztondo, Maria Victoria Salud M. (2007)
The purpose of this study was to design a school-based training program on classroom management for beginning science teachers of the Claret School of Quezon City (CSQC). Interviews were conducted for beginning teachers assigned to teach science classes in Grades 4 to 7 to determine their perceptions on what makes science different from the other subject areas, what are some of the common misbehavior they have encountered during the classes, and what they did to resolve them. A needs assessment was employed and yielded the ff areas of focus: lack of specialization in science teaching, lack of support for curriculum implementation, and lack of knowledge in the methods and materials in teaching science. This led to the researcher-designed school-based training program. It is composed of the information about the school, the science curriculum content, methodologies in teaching science including laboratory and classroom management during science classes, and mentoring support for the beginning science teachers.
"March 2007."
Thesis (M.A. Curriculum Studies)--University of the Philippines Diliman.
Keywords: Classroom management -- Philippines -- Quezon City; Science teachers -- Training of -- Philippines -- Quezon City; Science -- Study and teaching (Elementary) -- Philippines -- Quezon City